Implementasi Metode Waterfall Pada Rancang Bangun Sistem Informasi Akuntansi Penerimaan dan Pengeluaran Kas - Nurmalasari Nurmalasari; Anna Anna; Resty Ariyanti (LPPM Universitas Bina Sarana Informatika, 2021)
Recording of all cash receipts and disbursements transactions at CV. Malianury Grafiti was written into notes and recapitulated one by one. Of course this can cause several problems to arise. Starting from recording errors, data is not safe if it is stored in physical documents, reporting is sometimes inaccurate and takes a long time because the master data is processed manually. Therefore, an application is needed for systematic transaction data management. The accounting information system for cash receipts and payments uses the waterfall method. So that this system can help CV. Malianury Grafiti in managing cash receipt and disbursement transactions as well as making transaction reports and financial reports.